11x=9=6x-1

Simple and best practice solution for 11x=9=6x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x=9=6x-1 equation:



11x=9=6x-1
We move all terms to the left:
11x-(9)=0
We move all terms containing x to the left, all other terms to the right
11x=9
x=9/11
x=9/11

See similar equations:

| 77=y^2+2 | | y–2.3=7.8 | | 6x+17=70 | | 0.75a-4=0.25a | | -3+x2=-19 | | -8+n/5=-5 | | 2=14−3z | | x+2/4=x+5/5 | | 14=-2v+-6 | | -8+6m=0.5(-4m+16) | | 8x-13=4x+5+2x8x−13=4x+5+2x | | 2-4m=-2 | | 12m-10=82 | | 25/c+8=87 | | 3x-22+9x=2 | | 10-8x=2x=4x | | 13-5m=4-m | | 2z=9=15 | | -91=-7r | | 25c+3=8 | | 13=2t+7 | | 13=2+t7 | | -6x-10=2x+14 | | 3(5c+1)-12=13c+3Q | | 3x-4=-1x+8 | | 4n÷2=6 | | -2-h=-9 | | 2.8-y+y=4 | | n1=-3+ | | 5^x=300000 | | -2-5k=10 | | 8+b=-1 |

Equations solver categories